2013
DOI: 10.1111/gbi.12043
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of biogenic iron oxides records microbial physiology and environmental conditions: toward interpreting iron microfossils

Abstract: Despite the abundance of Fe and its significance in Earth history, there are no established robust biosignatures for Fe(II)-oxidizing micro-organisms. This limits our ability to piece together the history of Fe biogeochemical cycling and, in particular, to determine whether Fe(II)-oxidizers played a role in depositing ancient iron formations. A promising candidate for Fe(II)-oxidizer biosignatures is the distinctive morphology and texture of extracellular Fe(III)-oxyhydroxide stalks produced by mat-forming mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
77
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 64 publications
(104 reference statements)
12
77
1
Order By: Relevance
“…These Fe structures resemble those of Fe stalks produced by the known lithotrophic Fe(II)-oxidizing bacteria Mariprofundus ferrooxydans previously reported in deep sea hydrothermal environments (Juniper and Tebo, 1995;Fortin et al, 1998;Kennedy et al, 2003;Fleming et al, 2013). The twisted morphology is proposed to be resulted from cell rotation during the growth of lithotrophic Fe(II)-oxidizing bacteria for sensing the optimal location in the chemical gradients (Chan et al, 2011), while the branching pattern may be derived from cell division (Krepski et al, 2013). Fluorescent microscopy images of the Fe stalk structures stained with SYBR Green I reveal that bean-shaped cells are commonly positioned at the end of Fe-rich structures, indicating that these Fe-rich structures are directly produced by the cells (Fig.4).…”
Section: Fe Stalks Produced By Lithotrophic Fe(ii)-oxidizing Bacteriasupporting
confidence: 66%
See 1 more Smart Citation
“…These Fe structures resemble those of Fe stalks produced by the known lithotrophic Fe(II)-oxidizing bacteria Mariprofundus ferrooxydans previously reported in deep sea hydrothermal environments (Juniper and Tebo, 1995;Fortin et al, 1998;Kennedy et al, 2003;Fleming et al, 2013). The twisted morphology is proposed to be resulted from cell rotation during the growth of lithotrophic Fe(II)-oxidizing bacteria for sensing the optimal location in the chemical gradients (Chan et al, 2011), while the branching pattern may be derived from cell division (Krepski et al, 2013). Fluorescent microscopy images of the Fe stalk structures stained with SYBR Green I reveal that bean-shaped cells are commonly positioned at the end of Fe-rich structures, indicating that these Fe-rich structures are directly produced by the cells (Fig.4).…”
Section: Fe Stalks Produced By Lithotrophic Fe(ii)-oxidizing Bacteriasupporting
confidence: 66%
“…The first convincing evidence for deep-sea communities of Fe(II)-oxidizing bacteria Mariprofundus ferrooxydans was found at Loihi Seamount (Emerson and Moyer, 2002), and it was subsequently shown that Fe(II)-oxidizing bacteria were abundant and formed the mat-like communities responsible for most of the deposition of biogenic Fe oxyhydroxides in marine hydrothermal systems (Kennedy et al, 2003;Emerson and Moyer, 2010;Toner et al, 2012). One remarkable feature of Mariprofundus ferrooxydans is their ability to produce twisted stalks or sheaths containing an organic component that controls the deposition of the Fe(III) metabolic byproducts of cell growth Chan et al, 2011;Krepski et al, 2013;Fleming et al, 2013;Bennett et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Although organo-mineral twisted stalks, as used in our study, are rather unique to microbial microaerophilic Fe(II) oxidation 21 , twisted structures might be produced under abiotic conditions 60 . We thus propose that if structures similar to twisted structures are found in natural, lithified sediments, these should be characterized using spectroscopy using our criteria for an FeOB origin, in combination with those of Krepski et al 18 for determining environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chan et al 21 demonstrated that twisted stalks are biological structures formed during cell growth and Fe(II) oxidation 21 . Stalks have thus been proposed as morphological biosignatures for FeOB 18,21 . As stalk formation is induced by O 2 in cultures of Gallionella ferruginea 22 , and occurs at O 2 concentrations as low as 3 mM in cultures of Mariprofundus ferrooxydans 18 , stalks could also serve as evidence for the presence of localized oxygen in ancient environments.…”
mentioning
confidence: 99%
“…However, because abiotic photochemical oxidation is thought to be a very minor Fe(II) oxidation pathway in Si-rich Archean oceans (Konhauser et al, 2007a), much emphasis has been placed on the above-mentioned biological pathways. Of the three types of organisms implicated, only microaerophilic Fe(II)-oxidizing bacteria leave distinct morphological indicators ("biosignatures") of their presence and activity in ancient settings: organic stalks, often twisted, that are coated with Fe(III) minerals (Chan et al, 2011;Krepski et al, 2013). Yet these biosignatures do not appear in the IF record until the late Paleoproterozoic (Cloud, 1965;Planavsky et al, 2009;Wilson et al, 2010), suggesting that microaerophilic FeOB were not involved in Archean Fe(II) oxidation.…”
Section: Introductionmentioning
confidence: 99%